ANTERIOR MAXILLARY IMMEDIATE IMPLANT AFTER EXTRACTION WITH CLOSE LOADING TEMPORARY CROWN - Dewi Lidya Ichwana; Mirza Aquaries (Fakultas Kedokteran Gigi Unjani, 2021)
Immediate implant placement after extraction is a dental implant treatment procedure reported in several case studies with satisfactory results for patients and less crestal bone loss around the implant. This case report describes the method of immediate implant placement after extraction. It directs temporary crown placement in a female patient with failed post-endodontic treatment restoration on the maxillary incisor. The procedure was performed under local anesthesia, preceded by tooth extraction and socket cleaning post-extraction, followed by the implant and bone grafting procedure, then finalized by provisionalization. The immediate implant procedure is a simple and time-saving technique. No second surgery is required, such as delayed implant procedure, but the operator's good analytical, diagnostic, and planning skills in its implementation. DOI : 10.54052/jhds.v1n2.p142-152